Physical and mechanical characterization of aggregates in Burkina Faso: implications for use as endogenous knowledge in civil engineering - Ouiminga, Abdoul Aziz; Lareba Ouedraogo , Adélaïde; Kouraogo , Patrice; Yerbanga , Mohamed; Kam , Sié (International Journal of Engineering and Technology, 2024)
Aggregates are the world's most widely exploited resource, surpassing even fossil fuels. They are mainly used for concrete production. On the one hand, due to restrictions on the use of river sand in some parts of the world to conserve river beds, demand for alternative fine aggregates in the construction sector has increased considerably. The need to characterize and continuously update local and site-specific information on crushed aggregates and natural sand, in order to stimulate optimal use, is essential. As a contribution to strengthening the use of local aggregates in civil engineering, this study focuses on the characterization of aggregates. The various analyses enabled us to determine properties such as specific weight, grading class, flattening coefficient (only for crushed aggregates) and sand cleanliness (sand equivalent). Densities (apparent and absolute) meet the specifications of standard NF EN 12620, which stipulates an apparent density of between 1300 kg/m³ and 1600 kg/m³ and an absolute density of between 2500 kg/m³ and 2700 kg/m³. The results revealed a fineness modulus of 1.8. In view of this result, the sand complies with the requirements of standard NF P 18-541, which sets a fineness modulus of between 1.8 and 3.2, depending on the deposit, and requires an optimum modulus of 2.5. The (LA) results for 5/15 and 15/25 aggregates give values of 20.2% and 28.8% respectively. Analysis of the results shows that the aggregates studied are acceptable for concrete production.